Reimagining Community Mental Health Care Services: Case Study of a Need Based Biopsychosocial Response Initiated During Pandemic - Sunder, Poornima; Vincent, Anu Sonia; Saju, Meenu K.; Moorthy, Anu S.; Paulose, Godson; Robins, Roshni; Prabhu, Anupama V.; Arun, M.; Rajah, Anita; Venkateswaran, Chitra (Frontiers in Psychiatry, 2021)
Community mental health systems worldwide have undergone transformation in order to accommodate enormous demands of the pandemic and its mitigation efforts. The pandemic created unprecedented challenges that required Mehac Foundation (further referred as Mehac), a not for profit organization based in Kerala, to reassess our care delivery model. The aim of this report is to present a flexible, need-based biopsychosocial response; a case study effectuated by the Non-Governmental Organization (NGO) with a focus on minimizing the impact of COVID 19 on vulnerable communities, while adhering to timely regulations issued by the government. The key aspect of our biopsychosocial response was implementation of a phased approach that was rooted in real time need identification. The strategies will be described under broad headings of (i) adaptations for maintaining continuity of care, (ii) identifying vulnerable subgroups and need based psychological response, (iii) exploring social dimensions of the pandemic and implementing strategies to address them, (iv) ensuring team well-being and enhancing skills to effectively respond to the challenges.